(untitled) (Tzintzun, Revista de Estudios Históricos, 2020)
Through the study of the narrative on the site of Puebla in 1863 in the novels El Sol de Mayo and Episodios Nacionales Mexicanos, the article seeks to show what were the reasons why a negative vision of General Jesus Gonzalez Ortega was constructed in these novels. character to whom the press of the time praised for having been a participant in one of the "most glorious pages of history". This negative view was the product of the political discredit attributed to the general, since he was not forgiven for seeking to succeed Benito Juarez as president.